What role for the European Union in the Western Sahara Conflict? - Sánchez, Carolina Jiménez (Africana Studia, 2020)
Recent developments in the Western Sahara conflict touch various changing elements in the peace process. For this reason, it is necessary to explore what is the current and future role of the European Union (“EU”) in one of the most geographically closed colonial controversies of this century. Being aware of the EU’s leadership in third countries peace processes, this paper will focus on its practice in this conflict, with special consideration of analogous cases, and its commercial relation with the Occupying power, Morocco. Keywords: Western Sahara Conflict, EU, Morocco, Self-determination.